Is Pre-operative Clipping of Scalp Hair Necessary for Craniotomies? - Maharjan, Shailesh; Thapa, Amit; Shakya, Bikram; KC, Bidur (Nepal Journal of Neuroscience, 2019)
Pre-operative clipping of scalp hair has-been practiced before craniotomies to decrease surgical site infections. In developing countries like ours, due to poor hygiene this may look genuine. However, with regular pre-operative part preparation practices we have tried avoiding clipping of hair in routine craniotomies.This study retrospectively studied patients undergoing craniotomies during the last four years at Kathmandu Medical College Teaching Hospital and compared two groups of patients; pre-operative part preparation practices group who did not have pre-operative hair clipped and the other group who had pre-operative hair clipped. Only patients who could be studied for over two weeks were included in the study. Patients with pre-existing scalp injuries were excluded. Endpoints studied were post-operative surgical site infections and need for debridement and re-suturing.Of the total 726 patients studied, 246underwent craniotomies with pre-operative part preparation practices and 480 had their hair clipped. Of the pre-operative part preparation practices group, three had surgical site infections compared to eight who had their hair clipped (p=0.641). The infection led to debridement and re-suturing in two patients of pre-operative part preparation practices and four in hair clipped group (p=0.946). These two groups were comparable for age (p=0.210), however, there was statistically significant differences in gender (p=0.001), type of lesion (p=0.000), pneumocephalus (p=0.000), skull base fracture (p=0.000) and use of peri-operative antibiotics (p=0.000). However, all the above mentioned significant parameters did not have any statistical significant relation with surgical site infection {gender (p=0.255), type of lesion (p=0.264), pneumocephalus (p=0.787), skull base fracture(p=0.584) and use of peri-operative antibiotics(p=0.100)}.Pre-operative clipping of hair does not avoid surgical site infections. Protocol based part preparation practices of scalp and post-operative head hygiene are important to avoid the surgical site infections.